PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI (PT. KALBE FARMA TBK) PERIODE 2010-2022 - Difah Ambar Citra Pratiwi; Andriyani Hapsari (Journal of Research and Publication Innovation, 2024)
This research aims to determine whether there is an influence of Capital Structure (Debt to Equity Ratio) on Company Value (Price Earning Ratio) partially, whether there is an influence of Profitability (Net Profit Margin) on Company Value (Price Earning Ratio) partially, whether there is an influence Capital Structure (Debt to Equity Ratio) and Profitability (Net Profit Margin) on Company Value (Price Earning Ratio) simultaneously in the pharmaceutical company PT. Kalbe Farma Tbk which is listed on the Indonesia Stock Exchange (BEI) for the 2010-2022 period. The research method used is a quantitative method with descriptive analysis techniques. The data used is secondary data in the form of annual financial reports at PT. Kalbe Farma Tbk, the data was tested using the Statistical Product Service and Solution (SPSS) application program version 27.0. The data analysis used is descriptive statistical tests, classical assumption tests, regression analysis, coefficient of determination, t test, f test. Based on the results of the model suitability test, it shows that partially the capital structure (Dear to Equity Ratio) does not have a significant effect on company value (Price Earning Ratio) where the calculated T is 0.407 < T table 2.262 with a significant level of 0.069 > 0.05 and partially Profitability ( Net Profit Margin) does not have a significant effect on Company Value (Price Earning ratio) where T calculated is -1.735 < T table 2.262 with a significance level of 0.111 > 0.05. Meanwhile, based on the simultaneous F Test, Capital Structure (Debt to Equity Ratio) and Profitability (Net Profit Margin) have no significant effect on Company Value (Price Earning Ratio) where F count is 2.138 > F table 4.10 with a significance value of 0.169 > 0, 05. Then the R Square value was obtained at 29.9% while the remaining 70.1% was influenced by other factors that were not explained by other variables in the research.